Positive electrode active material, method for preparing same, and positive electrode and lithium secondary

CN119836695APending Publication Date: 2025-04-15LG ENERGY SOLUTION LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202380063671.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-23
Filing Date
2023-12-21
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing positive electrode active materials are prone to breaking at high temperatures, resulting in an increase in side reactions of the electrolyte and an increase in gas production, which affects the life and performance of the battery.

Method used

A lithium composite transition metal oxide is used as the positive electrode active material, which contains an orientation structure in at least a portion of the secondary particles in which the long axis of the grain is arranged in the direction from the center of the secondary particles toward its surface, and forms a coating with a sequential increase in the Co/Ni molar ratio on the inside of the grain, the grain boundary and the surface of the secondary particles.

Benefits of technology

By optimizing the diffusion path of lithium ions and reducing the side reaction of the electrolyte, excellent life characteristics and low gas production volume at high temperatures are achieved, and the high-temperature performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119836695A_ABST
    Figure CN119836695A_ABST
Patent Text Reader

Abstract

The present invention relates to a positive electrode active material and a method for preparing the same, the positive electrode active material comprising: a lithium composite transition metal oxide; the present invention relates to: a secondary particle which is in the form of a secondary particle in which a plurality of crystal grains are aggregated, and which includes, in at least a portion of the secondary particle, an orientation structure in which the long axes of the crystal grains are arranged in a direction from the center of the secondary particle toward the surface thereof; and a coating layer formed on the surface of the secondary particles and containing Co element, in which the lithium composite transition metal oxide contains nickel and cobalt, when the ratio of the number of moles of cobalt to the number of moles of nickel in the crystal grains is C1, the ratio of the number of moles of cobalt to the number of moles of nickel at a grain boundary, which is an interface between the crystal grains, is C2, and the ratio of the number of moles of cobalt to the number of moles of nickel in the coating layer is C3, C1lt is satisfied; c21t; c3.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a positive electrode active material, a preparation method thereof, and a positive electrode and a lithium secondary battery containing the positive electrode active material. More specifically, it relates to a positive electrode active material that generates little gas at high temperatures and can achieve excellent high temperature life performance, a preparation method thereof, and a positive electrode and a lithium secondary battery both containing the positive electrode active material. Background Art

[0002] In recent years, with the technological development and increase in demand for mobile devices and electric vehicles, the demand for secondary batteries as energy sources has rapidly increased. Among such secondary batteries, lithium secondary batteries with high energy density and voltage, long cycle life and low self-discharge rate have been commercialized and widely used.

[0003] As positive electrode active materials for lithium secondary batteries, lithium transition metal oxides such as LiCoO have been developed. 2 Lithium cobalt oxide, LiNiO 2 Lithium nickel oxide, LiMnO 2 or LiMn 2 O 4 Lithium manganese oxide and LiFePO 4 In recent years, Li[Ni a Co b Mn c ]O 2 、Li[Ni a Co b Al c ]O 2 and Li[Ni a Co b Mn c Al d ]O 2 A lithium composite transition metal oxide containing two or more transition metals.

[0004] Among them, lithium composite transition metal oxides containing two or more transition metals are generally prepared in the form of spherical secondary particles in which tens to hundreds of primary particles are aggregated, and physical properties such as mobility of lithium ions or wettability of electrolytes vary according to the orientation form of the primary particles or the shape (aspect ratio) of the primary particles. Therefore, research has been conducted to control the particle structure of the positive electrode active material particles to improve the performance of the positive electrode active material.

[0005] Korean Patent Registration No. 10-1611784 (Patent Document 1) discloses a positive electrode active material in which the length of a primary particle in the a-axis direction is longer than its length in the c-axis direction, and the a-axis of the primary particle is oriented toward the center of the secondary particle, wherein the particles grow along a predetermined path while being adjacent to each other.

[0006] In the case of a positive electrode active material in which the primary particles are radially arranged toward the center of the secondary particles as described above, the lithium movement path in the secondary particles is shortened, thereby achieving the effect of promoting the insertion and extraction of lithium ions and reducing resistance. However, compared with positive electrode active materials in which the primary particles are arranged without orientation, positive electrode active materials in which the primary particles are radially arranged are easily broken during rolling, so there is a problem of increased side reactions with the electrolyte, thereby accelerating the degradation of the battery cell and increasing gas generation. In particular, the above-mentioned problem is particularly prominent when exposed to high temperatures. Summary of the invention

[0007] Technical issues

[0008] The present invention aims to solve the above-mentioned problems and aims to provide a positive electrode active material and a method for preparing the same, wherein at least a portion of the secondary particles comprises an oriented structure in which the long axis of the grains is arranged in a direction from the center of the secondary particles toward the surface thereof, so that the lithium mobility and resistance characteristics are excellent, and the Co / Ni molar ratio is formed to increase in the order of the interior of the grains, the interface (grain boundary) between the grains, and the coating on the surface of the secondary particles, so that excellent life characteristics and gas generation characteristics can be achieved even when exposed to high temperatures.

[0009] In addition, the present invention is directed to providing a positive electrode and a lithium secondary battery comprising the positive electrode active material.

[0010] Technical Solution

[0011] According to one embodiment, the present invention provides a positive electrode active material, which includes: a lithium composite transition metal oxide, which is in the form of secondary particles in which a plurality of crystal grains are aggregated and contains an oriented structure in which the long axes of the crystal grains are arranged in a direction from the center of the secondary particles toward the surface thereof; and a coating formed on the surface of the secondary particles and containing a Co element, wherein the lithium composite transition metal oxide contains nickel and cobalt, and when the ratio of the molar number of cobalt to the molar number of nickel in the crystal grains is C1, the ratio of the molar number of cobalt to the molar number of nickel at the grain boundaries as the interfaces between the crystal grains is C2, and the ratio of the molar number of cobalt to the molar number of nickel in the coating is C3, the positive electrode active material satisfies C1. <C2<C3。

[0012] According to another embodiment, the present invention provides a method for preparing a positive electrode active material, the method comprising: preparing a lithium composite transition metal oxide, the lithium composite transition metal oxide being in the form of secondary particles in which a plurality of crystals are aggregated and comprising an oriented structure in which the long axes of the crystals are arranged in a direction from the center of the secondary particles toward the surface thereof in at least a portion of the secondary particles; a first coating step of mixing the lithium composite transition metal oxide with a coating solution containing a cobalt element and then performing a first heat treatment on the lithium composite transition metal oxide; and a second coating step of dry-mixing the lithium composite transition metal oxide that has undergone the first coating and a coating raw material containing a Co element and then performing a second heat treatment on the lithium composite transition metal oxide.

[0013] According to still another embodiment, the present invention provides a positive electrode including the positive electrode active material of the present invention and a lithium secondary battery including the positive electrode.

[0014] Beneficial Effects

[0015] The positive electrode active material of the present invention includes an oriented structure in which the major axes of the crystal grains are arranged in a direction from the center of the secondary particle toward the surface thereof, so that the lithium diffusion path inside the particle is short, thereby achieving excellent lithium mobility and resistance characteristics.

[0016] In addition, the positive electrode active material of the present invention is formed so that the Co / Ni molar ratio increases in the order of the interior of the grain, the grain boundary as the interface between the grains, and the coating on the surface of the secondary particle, so that even if the particles are broken due to rolling, the side reaction with the electrolyte can be reduced to a minimum. Therefore, compared with the positive electrode active material having a typical oriented structure, the positive electrode active material can achieve excellent high temperature characteristics.

[0017] In the positive electrode active material of the present invention, a lithium composite transition metal oxide having an oriented structure is wet-coated using a Co-containing coating solution and then mixed with a Co coating material for dry coating so that the Co / Ni molar ratio increases in the order of the coating inside the grains of the positive electrode active material, the grain boundaries, and the surface of the secondary particles. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a SEM photograph of a cross section of the lithium composite transition metal oxide produced according to Preparation Example 1.

[0019] Figure 2 This is a SEM photograph of a cross section of the lithium composite transition metal oxide produced according to Preparation Example 2. DETAILED DESCRIPTION

[0020] It should be understood that the terms or words used in the specification and claims should not be interpreted as limited to having the meanings defined in commonly used dictionaries, but should be interpreted as having meanings and concepts consistent with the technical concept of the present invention based on the principle that the inventor can appropriately define the concepts of the terms to best interpret the invention.

[0021] In the present invention, the term "grain" refers to the smallest particle unit that is distinguished as a single block and does not appear to have a grain boundary when observed using a scanning electron microscope within a field of view of 5,000 to 20,000 times, and the grain may be composed of a single crystallite or a plurality of crystallites. In the present invention, the average particle size of the grains can be measured by measuring the size of each particle distinguished in the cross-sectional SEM data of the positive electrode active material particles and obtaining the arithmetic average thereof.

[0022] In the present invention, "secondary particles" refer to secondary structures formed by aggregation of a plurality of crystal grains.

[0023] In the present invention, the term "D 50 ” refers to the particle size at which 50% of the volume cumulative particle size distribution of the positive electrode active material powder is observed. 50 It can be measured by laser diffraction. For example, D 50 The measurement can be performed by the following process: the positive electrode active material powder is dispersed in a dispersion medium, and the mixture is then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000), and irradiated with an ultrasonic wave of about 28 kHz with an output of 60 W to obtain a volume cumulative particle size distribution diagram, and then the particle size corresponding to 50% of the volume cumulative amount is obtained.

[0024] In the present invention, "oriented structure" refers to a structure in which the long axis of the grains is arranged in the direction from the center of the secondary particle toward the surface thereof. In this case, "the long axis of the grains is arranged in the direction from the center of the secondary particle toward the surface thereof" means that the angle formed between the shortest line connecting the center of the secondary particle and its surface when passing through the corresponding grain and the long axis of the grain is in the range of -15° to 15°.

[0025] In the present invention, “aspect ratio of a crystal grain” refers to the ratio of the major axis length of a crystal grain to the minor axis length of the crystal grain, and “average aspect ratio” refers to the arithmetic mean of the aspect ratios of the crystal grains in a corresponding region.

[0026] Hereinafter, the present invention will be described in detail.

[0027] <Positive Electrode Active Material>

[0028] The positive electrode active material of the present invention includes: (1) a lithium composite transition metal oxide, and (2) a coating layer formed on the surface of secondary particles of the lithium composite transition metal oxide and containing a Co element.

[0029] The lithium composite transition metal oxide is in the form of secondary particles in which a plurality of crystal grains are aggregated, and contains an oriented structure in which the long axis of the crystal grains is arranged in a direction from the center of the secondary particles toward the surface thereof. At this time, "the long axis of the crystal grains is arranged in a direction from the center of the secondary particles toward the surface thereof" means that the angle formed between the shortest line connecting the center of the secondary particles and its surface when passing through the corresponding crystal grains and the long axis of the crystal grains is in the range of -15° to 15°. The long axis of the crystal grain refers to the longest line segment in the straight line connecting two points on the surface of the crystal grain when passing through the center of the corresponding crystal grain. The interface between the crystal grains in the secondary particles of the positive electrode active material becomes a diffusion path for lithium ions. If the crystal grains are arranged in a direction from the center of the secondary particles toward the surface thereof, the diffusion path of the lithium ions inside the secondary particles is shortened, thereby increasing the lithium mobility, and thus can have the effect of improving the output and / or resistance characteristics.

[0030] At the same time, the long axis of the crystal grains arranged in the direction from the center of the secondary particle toward the surface thereof may form an angle of -15° to 15°, preferably -10° to 10°, with the a-axis direction of the crystal structure. Since lithium ions move along the a-axis direction in the crystal grains, when the long axis of the crystal grains forms an angle of -15° to 15° with the a-axis direction of the crystal structure, the insertion and extraction of lithium ions are promoted, thereby having the effect of improving the output and / or resistance characteristics.

[0031] At the same time, the aspect ratio of the grains whose major axes are arranged in the direction from the center of the secondary particle toward the surface thereof may be 1.5 to 15, preferably 2 to 15, and more preferably 4 to 15. If the aspect ratio of the grains satisfies the above range, the contraction and expansion of the grains during charge and discharge mainly occur in the minor axis direction (i.e., the direction perpendicular to the grain arrangement direction), thereby minimizing the occurrence of cracks due to uneven contraction and expansion of the grains.

[0032] Meanwhile, the lithium composite transition metal oxide may have, but is not limited to, a core-shell structure including a core portion where crystal grains are aggregated without any specific orientation, and a shell portion where the major axes of the crystal grains are arranged in a direction from the center of the secondary particle toward the surface thereof.

[0033] The core portion is a region where crystal grains are disorderly aggregated without any specific orientation, and is formed at the center of the secondary particle. The core portion may be a portion formed as a seed during a coprecipitation reaction for forming a precursor for a positive electrode active material, for example, if the radius of the secondary particle from the center of the secondary particle is set to R, it may be a region from the center of the secondary particle to a distance of 1 / 3R, or a region from the center of the secondary particle to a distance of 1 / 4R.

[0034] The crystal grains in the core portion may have a nearly spherical shape, and may have an aspect ratio of 0.7 to 1.3, preferably 0.8 to 1.2.

[0035] Next, a shell portion is formed outside the core portion, and the crystal grains are arranged in an oriented structure. The shell portion may be a portion formed by the growth of particles during a coprecipitation reaction for forming a precursor for a positive electrode active material, for example, if the radius of the secondary particle from the center of the secondary particle is set to R, it may be a region with a distance of 1 / 3R to R of the secondary particle, or a region with a distance of 1 / 4R to R of the secondary particle.

[0036] The crystal grains in the shell portion may have a rod shape, and may preferably have an aspect ratio of 2 to 15, more preferably 4 to 15.

[0037] Meanwhile, in the positive electrode active material of the present invention, the average particle size of the crystal grains may be 0.05 μm to 4 μm, preferably 0.1 μm to 3 μm, and more preferably 0.1 μm to 2 μm. If the average particle size of the crystal grains is too large, a rock salt phase is formed, so the resistance characteristics and life characteristics may be deteriorated, and if the average particle size of the crystal grains is too small, the contact area with the electrolyte increases, which may lead to rapid degradation.

[0038] The lithium composite transition metal oxide contains nickel and cobalt and may have a composition represented by, for example, the following [Formula 1].

[0039] [Formula 1]

[0040] Li x [Ni a Co b M 1 c M 2 d ]O 2-y A y

[0041] In the above [Formula 1], M 1 It may be one or more elements selected from the group consisting of Mn and Al, and for example, may be Mn or a combination of Mn and Al.

[0042] M 2 It can be one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Ta, Y, In, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo.

[0043] In addition, A may be one or more elements selected from the group consisting of F, Cl, Br, I, At and S.

[0044] x represents the ratio of the number of moles of Li to the total number of moles of transition metals, and can be 0.98 ≤ x ≤ 1.20, preferably 0.99 ≤ x ≤ 1.10, more preferably 1.0 ≤ x ≤ 1.10.

[0045] a represents the ratio of the number of moles of Ni to the total number of moles of all metals except lithium, and can be 0 < a < 1, preferably 0.3 ≤ a < 1, more preferably 0.6 ≤ a < 1, even more preferably 0.8 ≤ a < 1, still even more preferably 0.85 ≤ a < 1.

[0046] b represents the ratio of the number of moles of Co to the total number of moles of all metals except lithium, and can be 0 < b < 1, preferably 0 < b < 0.7, more preferably 0 < b < 0.4, even more preferably 0 < b < 0.2, still even more preferably 0 < b ≤ 0.1.

[0047] c represents M 1 the ratio of the number of moles of to the total number of moles of all metals except lithium, and can be 0 < c < 1, preferably 0 < c < 0.7, more preferably 0 < c < 0.4, even more preferably 0 < c < 0.2, still even more preferably 0 < c ≤ 0.1.

[0048] d represents M 2 the ratio of the number of moles of to the total number of moles of all metals except lithium, and can be 0 ≤ d ≤ 0.2, preferably 0 ≤ d ≤ 0.15, more preferably 0 ≤ d ≤ 0.10.

[0049] y represents the molar ratio of element A substituted at the oxygen site, and can be 0 ≤ y ≤ 0.2, preferably 0 ≤ y ≤ 0.15, more preferably 0 ≤ y ≤ 0.10.

[0050] Meanwhile, the lithium composite transition metal oxide includes a coating containing Co element on at least a part of the surface of the secondary particles. If a coating is formed on the surface of the lithium composite transition metal oxide, the contact between the lithium composite transition metal oxide and the electrolyte is suppressed by the coating, thereby reducing side reactions with the electrolyte, and thus the effect of improving the life characteristics can be achieved. In particular, if the coating contains Co element, the effect of reducing the initial resistance is more excellent compared with when other coating elements are included.

[0051] The shape or area of the coating is not particularly limited. For example, the coating can be in the form of a continuous film surrounding the entire surface of the secondary particles, or can be in the form of particles discontinuously distributed on the surface of the secondary particles. In addition, based on the total surface area of the secondary particles, the area of the region where the coating is formed can be 10% to 100%, 10% to 80%, or 20% to 70%.

[0052] The coating can be an oxide containing lithium and cobalt, and can have a composition represented by, for example, the following [Formula 2].

[0053] [Formula 2]

[0054] Li z Co 1-w M 3 w O 2

[0055] In [Formula 2], M 3 may be one or more selected from the group consisting of Ni, Mn, Al, W, Cu, Fe, V, Cr, Ti, Zr, Zn, Ta, Y, In, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and may be 0.8 ≤ z ≤ 1.2 and 0 ≤ w ≤ 0.2. Preferably, M 3 may be one or more selected from the group consisting of Ni, Mn, Al, Ti, Zr, and Mg, and may be 0.8 ≤ z ≤ 1.1 and 0 ≤ w ≤ 0.1.

[0056] When the coating satisfies the above composition, it can have the effect of improving the initial resistance characteristics and high-temperature life.

[0057] Meanwhile, when the ratio of the number of moles of cobalt to the number of moles of nickel in the crystal grains is C1, the ratio of the number of moles of cobalt to the number of moles of nickel at the grain boundary which is the interface between the crystal grains is C2, and the ratio of the number of moles of cobalt to the number of moles of nickel in the coating is C3, the positive electrode active material of the present invention satisfies C1 < C2 < C3. If the Co / Ni molar ratio at the grain boundary is higher than the Co / Ni molar ratio inside the crystal grains as in the present invention, it can have the effect of improving the particle strength by Co present at the grain boundary, thus suppressing particle breakage caused by roll pressing. In addition, in the case of secondary particles in which the crystal grains are arranged in an oriented manner as in the present invention, compared with secondary particles without grain orientation, side reactions with the electrolyte and surface deterioration occur more frequently on the surface of the secondary particles. However, if a high Co / Ni molar ratio is formed on the surface as in the present invention, it can have the effect of reducing side reactions with the electrolyte and deterioration on the surface of the secondary particles. That is, if the Co / Ni molar ratio satisfies the above conditions, particle breakage and side reactions with the electrolyte on the surface of the secondary particles can be minimized, and thus excellent high-temperature characteristics can be achieved compared with positive electrode active materials having a typical oriented structure. The D of the positive electrode active material 50 can be 2 μm to 25 μm, preferably 2 μm to 20 μm, more preferably 4 μm to 18 μm.

[0058] If the D of the positive electrode active material 50 satisfies the above range, it is possible to prevent the positive electrode active material particles from breaking during the roll pressing process or the processability from deteriorating during the slurry preparation.

[0059] <Preparation method of positive electrode active material>

[0060] Next, a method for preparing the positive electrode active material of the present invention will be described.

[0061] The preparation method of the positive electrode active material of the present invention comprises: (1) preparing a lithium composite transition metal oxide, wherein the lithium composite transition metal oxide is in the form of secondary particles in which a plurality of crystals are aggregated and contains an oriented structure in which the long axes of the crystals are arranged in a direction from the center of the secondary particles toward the surface thereof in at least a portion of the secondary particles; (2) mixing the lithium composite transition metal oxide with a coating solution containing a cobalt element and then performing a first coating step of a first heat treatment on the lithium composite transition metal oxide; and (3) dry mixing the lithium composite transition metal oxide subjected to the first coating and a coating raw material containing a cobalt element and then performing a second coating step of a second heat treatment on the lithium composite transition metal oxide.

[0062] (1) Steps for preparing lithium composite transition metal oxides

[0063] First, a lithium composite transition metal oxide having an oriented structure in which the major axes of crystal grains are aligned in a direction from the center of the secondary particle toward the surface thereof in at least a portion of the secondary particle is prepared. Specific specifications of the lithium composite transition metal oxide are the same as those described above.

[0064] The above-mentioned lithium composite transition metal oxide including an oriented structure may be prepared by purchasing a commercially available product, or may be prepared using a method for preparing a lithium composite transition metal oxide known in the art.

[0065] For example, a lithium composite transition metal oxide can be prepared by the following process: a metal solution containing nickel and cobalt elements, an ammonium cation complex former and an alkaline compound are injected into a reactor and a coprecipitation reaction is carried out to prepare a precursor for a positive electrode active material, and then the precursor for the positive electrode active material is mixed with a lithium raw material, and then the mixture is calcined.

[0066] The metal solution can be prepared by dissolving a nickel raw material and a cobalt raw material in a solvent such as water. The nickel raw material can be nickel acetate, carbonate, nitrate, sulfate, halide, sulfide or oxide, etc. Specifically, NiO, NiCO 3 ·2Ni(OH) 2 ·4H 2 O、NiC 2 O 2 ·2H 2 O.Ni(NO 3 ) 2 6H 2 O、NiSO 4 、NiSO 4 6H 2O, nickel halide or a combination thereof, but not limited thereto. The cobalt raw material may be acetate, carbonate, nitrate, sulfate, halide, sulfide or oxide of cobalt metal, and specifically, CoSO 4 、Co(OCOCH 3 ) 2 ·4H 2 O、Co(NO 3 ) 2 6H 2 O. CoSO 4 7H 2 O or a combination thereof, but not limited thereto.

[0067] The ammonium cation complex forming agent may be selected from NH 4 OH, (NH 4 ) 2 SO 4 NH 4 NO 3 NH 4 Cl, CH 3 COONH 4 and NH 4 CO 3 At least one of the group consisting of, and the compound can be introduced into the reactor in the form of a solution in which the compound is dissolved in a solvent. At this time, the solvent can be water, or a mixture of an organic solvent (such as alcohol, etc.) that can be uniformly mixed with water and water.

[0068] In addition, the alkaline compound may be selected from the group consisting of NaOH, KOH and Ca(OH) 2 At least one of the group consisting of, and the compound can be introduced into the reactor in the form of a solution in which the compound is dissolved in a solvent. At this time, the solvent can be water, or a mixture of an organic solvent (such as alcohol, etc.) that can be uniformly mixed with water and water.

[0069] At the same time, in order to prepare a positive electrode active material having an oriented structure as in the present invention, it is necessary to use a positive electrode active material precursor having an oriented structure in which primary particles are arranged in a direction from the center of the secondary particles toward the surface thereof. The aggregation form of the primary particles of the positive electrode active material precursor is affected by the pH, stirring rate, reaction temperature, etc. during the coprecipitation reaction. Therefore, when preparing a positive electrode active material precursor, the pH, stirring rate, reaction temperature, etc. can be appropriately adjusted to form a positive electrode active material precursor having an oriented structure, and by using the precursor, a lithium composite transition metal oxide having an oriented structure can be prepared.

[0070] Meanwhile, when preparing the lithium composite transition metal oxide of the present invention, M 1 Elements and M 2The element may be introduced in the coprecipitation reaction step for preparing the precursor for the positive electrode active material, or may be introduced during the mixing of the lithium raw material. In addition, when two or more elements are used as M 1 Elements and M 2 When the element M 1 Elements and M 2 The timing of introduction of each element may be the same or different. For example, when Mn and Al are included as M 1 When adding elements, Mn can be introduced in the precursor co-precipitation step, and Al can be introduced in the mixing step with the lithium raw material.

[0071] M can be appropriately adjusted in consideration of the final composition of the positive electrode active material to be prepared. 1 Elements and M 2 Timing of introduction of elements. For example, in the case of preparing a positive electrode active material having a Ni content of 80 atomic % or more, it is more preferred to introduce the Al element in the mixing step with the lithium raw material rather than during the coprecipitation reaction. This is because the introduction of Al in the coprecipitation step may have an adverse effect on the growth of the crystal structure.

[0072] The lithium raw material and the positive electrode active material precursor may be mixed so that the molar ratio of Li: all transition metals in the precursor is 1: 1 to 1.2: 1, preferably 1: 1 to 1.1: 1. If the mixing ratio of the lithium raw material to the transition metal in the positive electrode active material precursor satisfies the above range, the crystal structure of the positive electrode active material is well developed, and thus a positive electrode active material having excellent capacity characteristics and structural stability can be prepared.

[0073] The lithium raw material may be, for example, a carbonate (e.g., lithium carbonate), a hydrate (e.g., lithium hydroxide hydrate (LiOH·H 2 O) etc.), hydroxides (e.g., lithium hydroxide, etc.), nitrates (e.g., lithium nitrate (LiNO 3 ) etc.) and chlorides (e.g., lithium chloride (LiCl) etc.), etc., and any one of them or a mixture of two or more thereof can be used.

[0074] The calcination can be performed at an appropriate temperature in consideration of the composition of the lithium composite transition metal oxide, for example, at 600° C. to 1000° C., preferably 700° C. to 900° C. The calcination time can be, for example, 5 to 30 hours, preferably 8 to 15 hours, but is not limited thereto.

[0075] (2) First coating step

[0076] When preparing a lithium composite transition metal oxide including an oriented structure, a first coating step of mixing the lithium composite transition metal oxide with a coating solution containing a cobalt element and then subjecting it to a first heat treatment is performed.

[0077] The coating solution containing the cobalt element can be prepared by adding a selected from CoNO 3 、Co(NO 3 ) 2 6H 2 O、CoCl 2 、CoSO 4 、Co(OCOCH 3 ) 2 ·4H 2 O and Co(OH) 2 The composition is prepared by dissolving one or more of the components in a solvent such as water or ethanol.

[0078] When the first coating is performed by a wet coating method in which a coating solution and a lithium composite transition metal oxide are mixed and then heat treated as described above, the cobalt element contained in the coating solution not only penetrates the surface of the secondary particles of the lithium composite transition metal oxide, but also penetrates the interface (grain boundary) between the grains, so that the cobalt concentration at the grain boundary can be formed to be higher than the cobalt concentration inside the grain.

[0079] Meanwhile, the first heat treatment may be performed at 300°C to 800°C, preferably 400°C to 700°C, and more preferably 500°C to 650°C. When the first heat treatment temperature satisfies the above range, the cobalt element contained in the coating solution is concentrated at the grain boundary, so that the ratio of the molar number of cobalt to the molar number of nickel at the grain boundary can be formed to be higher than that inside the grain. If the first heat treatment temperature is too low, the coating cannot be performed smoothly, and if the first heat treatment temperature is too high, the cobalt will diffuse into the grains without being concentrated at the grain boundary.

[0080] (3) Second coating step

[0081] Next, a second coating step is performed in which the first-coated lithium composite transition metal oxide and a coating raw material containing a Co element are dry-mixed and then subjected to a second heat treatment.

[0082] The coating material containing cobalt element may be selected from Co(OH) 2 , CoO, Co 2 O 3 、Co 3 O 4 , CoO(OH) and Co(OCOCH 3 ) 2 One or more of the groups consisting of.

[0083] If the coating is performed in a dry manner as described above, unlike the wet coating, the cobalt element less penetrates into the interface between the grains and remains on the surface of the secondary particles, thereby contributing to the formation of a coating on the surface of the secondary particles. Therefore, the cobalt element introduced during the first coating and the cobalt element introduced during the second coating accumulate on the surface of the secondary particles, so that the ratio of the molar number of cobalt to the molar number of nickel on the surface of the secondary particles becomes higher than that at the grain boundaries.

[0084] Meanwhile, the second heat treatment step may be performed at 300°C to 800°C, preferably 400°C to 700°C, and more preferably 500°C to 700°C. If the second heat treatment temperature satisfies the above range, the cobalt concentration on the surface of the secondary particles may be formed to be higher than the cobalt concentration on the grain boundaries. If the second heat treatment temperature is too low, coating may not proceed smoothly, and if the second heat treatment temperature is too high, cobalt may diffuse into the grain boundaries and / or grains, making it difficult to form a high cobalt concentration on the surface of the secondary particles.

[0085] <Positive electrode>

[0086] Next, the positive electrode of the present invention will be described.

[0087] The positive electrode includes the positive electrode active material of the present invention. Specifically, the positive electrode includes a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector, wherein the positive electrode active material layer includes the positive electrode active material of the present invention.

[0088] At this time, since the positive electrode active material is the same as described above, a detailed description thereof will be omitted, and only the remaining components will be described in detail hereinafter.

[0089] The positive electrode current collector may include a highly conductive metal, without particular limitation, as long as it is non-reactive within the voltage range of the battery and the positive electrode active material layer can be easily adhered to the positive electrode current collector. As the positive electrode current collector, for example, stainless steel, aluminum, nickel, titanium, sintered carbon, or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium and silver, etc., may be used. Moreover, the thickness of the positive electrode current collector may generally be 3 μm to 500 μm, and fine concavoconvexities may be formed on the surface of the current collector to improve the adhesion of the positive electrode active material. For example, the positive electrode current collector may be used in various forms, such as films, sheets, foils, nets, porous bodies, foams and non-woven fabrics.

[0090] In addition to the positive electrode active material, the positive electrode active material layer may optionally contain a conductive material, a binder, and the like, as necessary.

[0091] At this time, the positive electrode active material may be contained in an amount of 80 wt % to 99 wt %, more specifically 85 wt % to 98.5 wt %, based on the total weight of the positive electrode active material layer. When included within the above content range, excellent capacity characteristics may be exhibited.

[0092] The conductive material is used to impart conductivity to the electrode, and any conductive material can be used without particular limitation, as long as it has electronic conductivity without causing chemical changes in the constituted battery. Specific examples thereof may include: graphite, such as natural graphite or artificial graphite; carbon-based materials, such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive tubes, such as carbon nanotubes; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; or conductive polymers, such as polyphenylene derivatives, and any one thereof or a mixture of two or more thereof may be used. The content of the conductive material may be 0.1 wt % to 15 wt % based on the total weight of the positive electrode active material layer.

[0093] Binder is used to improve the bonding between the positive active material particles and the adhesion between the positive active material and the current collector. Its specific examples may include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, polymethyl methacrylate, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, polyacrylic acid, hydrogen is replaced by Li, Na or Ca polymer or its various copolymers, and any one or a mixture of two or more thereof can be used. Based on the total weight of the positive active material layer, the content of the binder can be 0.1 wt % to 15 wt %.

[0094] In addition to using the above-mentioned positive electrode active material, the positive electrode can be prepared according to a typical method for manufacturing a positive electrode. Specifically, the positive electrode can be prepared by coating a positive electrode slurry composition prepared by dissolving or dispersing the above-mentioned positive electrode active material and, if necessary, an optional binder, a conductive material, and a dispersant in a solvent on a positive electrode current collector, and then drying and rolling to prepare the positive electrode.

[0095] The solvent may be a commonly used solvent in the art, and may be dimethyl sulfoxide (DMSO), isopropanol, N-methylpyrrolidone (NMP), dimethylformamide (DMF), acetone or water, etc., and any one thereof or a mixture of two or more thereof may be used. If the solvent dissolves or disperses the positive electrode active material, the conductive material, the binder and the dispersant in consideration of the coating thickness and manufacturing yield of the slurry, and thereafter the slurry is made to have a viscosity capable of showing excellent thickness uniformity when the coating of the positive electrode is manufactured, the amount of the solvent is sufficient.

[0096] In addition, in another method, the positive electrode can also be manufactured by casting the positive electrode slurry composition on a separate support and then laminating a film obtained by peeling off the support on a positive electrode current collector.

[0097] <Electrochemical Device>

[0098] The present invention can manufacture an electrochemical device including a positive electrode. Specifically, the electrochemical device can be a battery or a capacitor, and more specifically, a lithium secondary battery.

[0099] Specifically, the lithium secondary battery may include a positive electrode, a negative electrode disposed opposite to the positive electrode, a separator between the positive electrode and the negative electrode, and an electrolyte. Since the positive electrode is the same as above, its detailed description will be omitted, and only the remaining components will be described in detail below.

[0100] Also, the lithium secondary battery may optionally further include a battery case for accommodating an electrode assembly consisting of a positive electrode, a negative electrode, and a separator, and a sealing member for sealing the battery case.

[0101] In the above lithium secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.

[0102] The negative electrode current collector is not particularly limited as long as it has high conductivity without causing chemical changes in the battery, for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with one of carbon, nickel, titanium and silver, and aluminum-cadmium alloys, etc. can be used. Moreover, the thickness of the negative electrode current collector can generally be 3 μm to 500 μm, and as in the case of the positive electrode current collector, fine concavoconvexities can be formed on the surface of the current collector to improve the adhesion of the negative electrode active material. For example, the negative electrode current collector can be used in various forms, such as a film, a sheet, a foil, a net, a porous body, a foam and a non-woven fabric body.

[0103] The negative electrode active material layer may optionally contain a binder and a conductive material in addition to the negative electrode active material.

[0104] As the negative electrode active material, a compound capable of reversibly intercalating and deintercalating lithium can be used. Specific examples thereof may include: carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, or amorphous carbon; metal compounds capable of alloying with lithium, such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloy, Sn alloy, or Al alloy; metal oxides that can be doped and dedoped with lithium, such as SiO β (0<β<2), SnO 2, vanadium oxide or lithium vanadium oxide; or a composite comprising a metal compound and a carbonaceous material, such as a Si-C composite or a Sn-C composite, and any one of them or a mixture of two or more thereof can be used. In addition, a metallic lithium film can be used as a negative electrode active material. In addition, low-crystalline carbon and high-crystalline carbon, etc. can be used as carbon materials. Representative examples of low-crystalline carbon may include soft carbon and hard carbon, and representative examples of high-crystalline carbon may include irregular, planar, flaky, spherical or fibrous natural graphite or artificial graphite, Kish graphite, pyrolytic carbon, mesophase pitch-based carbon fibers, mesophase carbon microbeads, mesophase pitch and high-temperature sintered carbon, such as coke derived from petroleum or coal tar pitch.

[0105] The negative electrode active material may be contained in an amount of 80 wt % to 99 wt % based on the total weight of the negative electrode active material layer.

[0106] The binder is a component used to assist the bonding between the conductive material, the active material and the current collector, and is generally added in an amount of 0.1 wt % to 10 wt % based on the total weight of the negative electrode active material layer. Examples of binders may include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile rubber, fluororubber and various copolymers thereof.

[0107] The conductive material is a component for further improving the conductivity of the negative electrode active material, and the amount thereof added may be 10% by weight or less, preferably 5% by weight or less, based on the total weight of the negative electrode active material layer. The conductive material is not particularly limited as long as it has conductivity and does not cause chemical changes in the battery, for example, graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; carbon fluoride; metal powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives, etc. may be used.

[0108] As an example, the negative electrode active material layer may be prepared by coating a negative electrode slurry composition prepared by dissolving or dispersing the negative electrode active material and optionally a binder and a conductive material in a solvent on a negative electrode collector, and then drying, or may be prepared by casting the negative electrode slurry composition on a separate support and then laminating a film peeled off from the support on the negative electrode collector.

[0109] Meanwhile, in the above-mentioned lithium secondary battery, the diaphragm is used to separate the negative electrode from the positive electrode and provide a mobile path for lithium ions, and any diaphragm commonly used as a diaphragm in a lithium secondary battery can be used without particular limitation, in particular, preferably a diaphragm having a high moisture retention capacity for the electrolyte while having low resistance to the movement of electrolyte ions. Specifically, a porous polymer film can be used, for example, a porous polymer film made using a polyolefin polymer (such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer or an ethylene / methacrylate copolymer), or a stacked structure having more than two layers thereof. Moreover, a typical porous nonwoven fabric can be used, such as a nonwoven fabric made of glass fiber or polyethylene terephthalate fiber with a high melting point. Moreover, a coated diaphragm including a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and can be selectively used with a monolayer or multilayer structure.

[0110] In addition, the electrolyte used in the present invention may be an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel polymer electrolyte, a solid inorganic electrolyte or a molten inorganic electrolyte that can be used to manufacture a lithium secondary battery, but is not limited thereto.

[0111] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0112] As the organic solvent, any organic solvent can be used without particular limitation, as long as it can act as a medium through which ions participating in the electrochemical reaction of the battery can move. Specifically, as the organic solvent, ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone or ε-caprolactone can be used; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene or fluorobenzene; carbonate solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC) or propylene carbonate (PC); alcohol solvents such as ethanol or isopropanol; nitriles such as R-CN (wherein R is a linear, branched or cyclic hydrocarbon group having 2 to 20 carbon atoms, and may include a double bond aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; or cyclopentane sulfones, etc. can be used. Among the above-mentioned solvents, carbonate solvents are preferred, and more preferably a mixture of cyclic carbonates (e.g., ethylene carbonate or propylene carbonate) with high ionic conductivity and high dielectric constant and low viscosity straight-chain carbonate compounds (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate, etc.) which can improve the charge and discharge characteristics of the battery.

[0113] As the lithium salt, any compound can be used without particular limitation as long as it can provide lithium ions used in lithium secondary batteries. Specifically, the anion of the lithium salt can be selected from F - , Cl - Br - ,I - 、NO 3 - 、N(CN) 2 - , BF 4 - CF 3 CF 2 SO 3 - ,(CF 3 SO 2 ) 2 N - 、(FSO 2 ) 2 N - CF 3 CF 2 (CF 3 ) 2 CO - ,(CF 3 SO 2 ) 2 CH - , (SF 5 ) 3 C - ,(CF 3 SO 2 ) 3 C - CF 3 (CF 2 ) 7 SO 3 - CF 3 CO 2 - , CH 3 CO 2 - 、SCN - and (CF 3 CF 2 SO 2 ) 2 N - At least one of the group consisting of, and as the lithium salt, LiPF 6 、LiClO 4 、LiAsF 6 , LiBF 4 、LiSbF 6 、LiAlO4 、LiAlCl 4 、LiCF 3 SO 3 ,LiC 4 F 9 SO 3 、LiN(C 2 F 5 SO 3 ) 2 、LiN(C 2 F 5 SO 2 ) 2 、LiN(CF 3 SO 2 ) 2 , LiCl, LiI or LiB(C 2 O 4 ) 2 The lithium salt may be used in a concentration range of 0.1 M to 2.0 M. If the concentration of the lithium salt is included in the above range, the electrolyte has suitable conductivity and viscosity, and thus may exhibit excellent electrolyte performance, and lithium ions may be efficiently moved.

[0114] As described above, the lithium secondary battery including the cathode active material of the present invention exhibits excellent capacity characteristics and life characteristics, and can be effectively used in various fields such as portable devices (eg, mobile phones, notebook computers, and digital cameras) and electric vehicles.

[0115] Example

[0116] Hereinafter, the present invention will be described in more detail with reference to Examples. However, the embodiments of the present invention may be modified into other various forms, and the scope of the present invention should not be construed as being limited to the embodiments described below. Embodiments of the present invention are provided in order to more fully describe the present invention to those skilled in the art.

[0117] Preparation Example 1 - Preparation of Oriented Lithium Transition Metal Oxide

[0118] NiSO 4 、CoSO 4 and MnSO 4 The mixture was mixed in distilled water in an amount such that the molar ratio of nickel:cobalt:manganese was 8:1:1 to prepare an aqueous transition metal solution.

[0119] Subsequently, deionized water was added to the reactor, and then nitrogen was purged into the reactor to remove dissolved oxygen in the water, and NaOH was introduced to maintain the pH in the reactor at 11.

[0120] Thereafter, the transition metal aqueous solution, NaOH aqueous solution and NH 4The OH aqueous solution was introduced into the reactor to carry out a coprecipitation reaction at a reaction temperature of 50°C, a pH of 11, and a stirring rate of 400 rpm for 30 hours to prepare a granular material with an average particle size (D 50 ) is 12 μm for the positive electrode active material precursor Ni 0.8 Co 0.1 Mn 0.1 (OH) 2 At this time, the transition metal ions and NH 4 The molar ratio of OH is 1:1.10.

[0121] The positive electrode active material precursor and LiOH were mixed so that the molar ratio of Li:transition metal (Ni+Co+Mn) was 1.02:1, and then calcined at 730° C. for 20 hours, washed with water, and dried to prepare a lithium composite transition metal oxide.

[0122] exist Figure 1 , a scanning electron microscope (SEM) image of a cross section of the lithium composite transition metal oxide prepared as described above is shown. Figure 1 It can be seen that the lithium composite transition metal oxide prepared by the above method is in the form of secondary particles in which a plurality of crystal grains are aggregated, and the major axes of the crystal grains are aligned in a direction from the center of the secondary particle toward the surface thereof.

[0123] Preparation Example 2 - Preparation of non-oriented lithium transition metal oxide

[0124] In addition to introducing transition metal aqueous solution, NaOH aqueous solution and NH 4 OH aqueous solution makes the transition metal react with NH 4 The molar ratio of OH was 1:0.8, and the coprecipitation reaction was carried out under the conditions of reaction temperature of 60°C, pH of 11, stirring rate of 300 rpm, and calcination was carried out at 750°C. The lithium composite transition metal oxide was prepared in the same manner as Preparation Example 1.

[0125] exist Figure 2 , a scanning electron microscope (SEM) image of a cross section of the lithium composite transition metal oxide prepared as described above is shown. Figure 2 It can be seen that the lithium composite transition metal oxide prepared by the above method is in the form of secondary particles in which a plurality of crystallites are aggregated, and the crystallites are arranged in a disordered manner without any specific orientation.

[0126] Example

[0127] Will Co(NO 3 ) 2 6H 2 O was dissolved in deionized water (DI water) to prepare a Co-containing coating solution.

[0128] The lithium composite transition metal oxide prepared by Preparation Example 1 was introduced into the coating solution, stirred at 500 rpm for 3 hours, and then subjected to a first heat treatment at 600° C. (first coating step).

[0129] Next, lithium composite transition metal oxide and Co(OH) 2 The mixture was dry-mixed at a weight ratio of 1:0.002 and then subjected to a second heat treatment at 680° C. (second coating step) to prepare a positive electrode active material.

[0130] Comparative Example 1

[0131] A positive electrode active material was prepared in the same manner as in Example 1, except that the lithium composite transition metal oxide prepared in Preparation Example 2 was used instead of the lithium composite transition metal oxide prepared in Preparation Example 1.

[0132] Comparative Example 2

[0133] A positive electrode active material was prepared in the same manner as in Example 1, except that only the first coating step was performed, and the second coating step was not performed.

[0134] Comparative Example 3

[0135] A positive electrode active material was prepared in the same manner as in Example 1, except that only the second coating step was performed without performing the first coating step.

[0136] Comparative Example 4

[0137] The lithium composite transition metal oxide prepared in Preparation Example 1 and Co(OH) 2 The dry-mixed materials were mixed at a weight ratio of 1:0.002 and heat-treated at 680° C. to form a coating.

[0138] Thereafter, Co(NO 3 ) 2 6H 2 O was dissolved in deionized water (DI water) to prepare a Co-containing coating solution, and the lithium composite transition metal oxide having the coating layer formed thereon was introduced into the Co-containing coating solution, stirred at 500 rpm for 3 hours, and then heat-treated at 600° C. to prepare a positive electrode active material.

[0139] Experimental Example 1: Co concentration measurement

[0140] Energy dispersive X-ray spectrometer (EDX) was used to measure the Co / Ni molar ratio inside the grains, at the grain boundaries, and on the secondary particle surfaces of the positive electrode active materials prepared in each of Example and Comparative Examples 1 to 3. The measurement results are shown in Table 1 below.

[0141] <Manufacturing of lithium secondary batteries>

[0142] The positive electrode active material, conductive material (Denka black) and binder (PVDF) prepared in each of Examples and Comparative Examples 1 to 4 were mixed in a weight ratio of 96:2:2 in N-methyl-2-pyrrolidone (NMP) as a solvent to prepare a positive electrode slurry. The positive electrode slurry was coated on one surface of an aluminum current collector, dried, and then rolled to manufacture a positive electrode.

[0143] Next, the negative electrode active material (natural graphite), the conductive material (carbon black) and the binder (PVDF) were mixed in a weight ratio of 96:2:2 in N-methylpyrrolidone as a solvent to prepare a negative electrode slurry. The negative electrode slurry composition was coated on a copper current collector, dried, and then rolled to make a negative electrode.

[0144] A separator was inserted between the positive electrode and the negative electrode to produce an electrode assembly, and the electrode assembly was placed inside a battery case, and then an electrolyte was injected therein to produce a lithium secondary battery. At this time, as an electrolyte, 1 M LiPF 6 The electrolyte is dissolved in an organic solvent of ethylene carbonate:ethyl methyl carbonate mixed in a volume ratio of 3:7.

[0145] Experimental Example 2: High Temperature Life Characteristics

[0146] The lithium secondary batteries manufactured as described above were each charged to 4.2V at a constant current of 1C at 45°C and then discharged to 2.5V at a constant current of 0.5C, which was set as one cycle, and 50 charge and discharge cycles were performed to measure the capacity retention rate. The measurement results are shown in [Table 1] below.

[0147] Experimental Example 3: Gas Generation During High-Temperature Storage

[0148] The lithium secondary batteries manufactured as described above were each charged to SOC 100, stored at 60°C for 8 weeks, and then perforated in a chamber of a vacuum atmosphere to exhaust the gas inside the battery and collect the gas inside the vacuum chamber, and the gas in the chamber was analyzed for gas generation using a gas chromatography-flame ionization detector (GC-FID). When the gas generation of the lithium secondary battery using the positive electrode active material of the embodiment is set to 100%, the ratio of the gas generation of the lithium secondary battery using the positive electrode active material of each of Comparative Examples 1 to 3 is shown in [Table 1] below.

[0149] Experimental Example 4: Initial Resistance

[0150] The lithium secondary batteries manufactured as described above were each charged to SOC 100, discharged for 10 seconds to measure the voltage change amount, and the measured voltage change amount was divided by the discharge current to measure the initial resistance value. The measurement results are shown in the following [Table 1].

[0151] [Table 1]

[0152]

[0153] As shown in Table 1 above, the Co / Ni molar ratio of the positive electrode active materials of the embodiment and comparative example 1 prepared by sequentially performing wet coating and dry coating increases in the order of the inside of the grain, the grain boundary, and the surface of the secondary particles, while the positive electrode active material of comparative example 2 prepared by only performing wet coating has the same level of Co / Ni molar ratio at the grain boundary and on the surface of the secondary particles, and the positive electrode active material of comparative example 3 prepared by only performing dry coating has the same level of Co / Ni molar ratio at the grain boundary and inside the grain. Meanwhile, the positive electrode active material of comparative example 4 prepared by first performing dry coating and then performing wet coating has a Co / Ni molar ratio at the grain boundary that is higher than the Co / Ni concentration in the coating.

[0154] In addition, it can be confirmed from Table 1 that, compared with the lithium secondary batteries using the positive electrode active materials of Comparative Examples 1 to 4, the lithium secondary batteries using the positive electrode active materials of the embodiments have excellent high temperature life characteristics and initial resistance characteristics, and the amount of gas generated after high temperature storage is less, thereby showing excellent high temperature characteristics.

Claims

1. A positive electrode active material comprising: A lithium composite transition metal oxide in the form of secondary particles aggregated from a plurality of grains and having an orientation structure in at least a part of the secondary particles, in which the major axes of the grains are arranged in a direction from the center of the secondary particles toward the surface thereof; and a coating formed on the surface of the secondary particles and containing a Co element, wherein: the lithium composite transition metal oxide contains nickel and cobalt; and when the ratio of the number of moles of cobalt to the number of moles of nickel in the grains is C1, the ratio of the number of moles of cobalt to the number of moles of nickel at the grain boundary as the interface between the grains is C2, and the ratio of the number of moles of cobalt to the number of moles of nickel in the coating is C3, C1 < C2 < C3 is satisfied.

2. The positive electrode active material according to claim 1, wherein An angle of -15° to 15° is formed between the major axis of the grain whose major axis is arranged in a direction from the center of the secondary particle toward the surface thereof and the a-axis direction of the crystal structure.

3. The positive electrode active material according to claim 1, wherein The aspect ratio of the grains whose major axes are arranged in a direction from the center of the secondary particles toward the surface thereof is 1.5 to 15.

4. The positive electrode active material according to claim 1, wherein The lithium composite transition metal oxide includes: a core part in which the grains are disorderly aggregated; and a shell part formed outside the core part and having grains arranged in an orientation structure.

5. The positive electrode active material according to claim 4, wherein The aspect ratio of the grains in the core part is 0.8 to 1.

2.

6. The positive electrode active material according to claim 4, wherein The aspect ratio of the grains in the shell part is 1.5 to 15.

7. The positive electrode active material according to claim 1, wherein The lithium composite transition metal oxide has a composition represented by the following formula 1: [Formula 1] Li x [Ni a Co b M 1 c M 2 d ]O 2-y A y wherein, in the above formula 1, M 1 is one or more elements selected from the group consisting of Mn and Al, M 2 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, Ta, Y, In, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo, A is one or more elements selected from the group consisting of F, Cl, Br, I, At, and S, and 0.98 ≤ x ≤ 1.20, 0 < a < 1, 0 < b < 1, 0 < c < 1, 0 ≤ d ≤ 0.2, and 0 ≤ y ≤ 0.

2.

8. The positive electrode active material according to claim 1, wherein The coating has a composition represented by the following formula 2: [Formula 2] Li z Yes 1-w M 3 w O2 Among them, in the above formula 2, M 3 It is one or more selected from the group consisting of Ni, Mn, Al, W, Cu, Fe, V, Cr, Ti, Zr, Zn, Ta, Y, In, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo, 0.8≤z≤1.2 and 0≤w≤0.

2.

9. The positive electrode active material according to claim 1, wherein The average particle size of the grains is 0.05 μm to 4 μm.

10. The positive electrode active material according to claim 1, wherein The positive electrode active material D 50 2μm to 20μm.

11. A method for preparing a positive electrode active material, the method comprising: preparing a lithium composite transition metal oxide in the form of secondary particles aggregated from a plurality of grains and having an orientation structure in at least a part of the secondary particles, in which the major axes of the grains are arranged in a direction from the center of the secondary particles toward the surface thereof; a first coating step of mixing the lithium composite transition metal oxide with a coating solution containing a cobalt element and then performing a first heat treatment on the mixture; and a second coating step of dry-mixing the lithium composite transition metal oxide after the first coating with a coating raw material containing a Co element and then performing a second heat treatment on the mixture.

12. The method according to claim 11, wherein: The coating solution containing a cobalt element is obtained by dissolving one or more selected from the group consisting of CoNO3, Co(NO3)2·6H2O, CoCl2, CoSO4, Co(OCOCH3)2·4H2O, and Co(OH)2 in water.

13. The method according to claim 11, wherein: The first heat treatment step is performed at 300°C to 800°C.

14. The method according to claim 11, wherein: The coating raw material containing a cobalt element is one or more selected from the group consisting of Co(OH)2, CoO, Co2O3, Co3O4, CoO(OH), and Co(OCOCH3)2.

15. The method according to claim 11, wherein: The second heat treatment step is performed at 300°C to 800°C. 16 . A positive electrode comprising the positive electrode active material according to claim 1 . 17 . A lithium secondary battery comprising the positive electrode according to claim 16 .

Citation Information

Patent Citations

  • Precursor for cathod active material of lithium secondary battery, cathode active materials made by the same, and lithium secondary battery containing the same

    KR101611784B1

  • Modified lithium nickel cobalt manganese cathode material and production method thereof

    CN107591519A

  • Composite cathode active material, cathode and lithium battery including the same, and method of preparing the composite cathode active material

    CN110556520A

  • High-nickel positive electrode material, preparation method thereof and lithium ion secondary battery

    CN112382741A

  • Positive electrode material, and preparation method and application thereof

    CN113823789A